2011
DOI: 10.1371/journal.pone.0027636
|View full text |Cite
|
Sign up to set email alerts
|

Exposing Racial Discrimination: Implicit & Explicit Measures–The My Body, My Story Study of 1005 US-Born Black & White Community Health Center Members

Abstract: BackgroundTo date, research on racial discrimination and health typically has employed explicit self-report measures, despite their potentially being affected by what people are able and willing to say. We accordingly employed an Implicit Association Test (IAT) for racial discrimination, first developed and used in two recent published studies, and measured associations of the explicit and implicit discrimination measures with each other, socioeconomic and psychosocial variables, and smoking.Methodology/Princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
95
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 77 publications
9
95
0
2
Order By: Relevance
“…This is significant, given that the literature on discrimination and (mental) health has emphasized unfair treatments attributed to race 5,34 . Even though a recent literature review has shown that many types of discrimination are harmful to health 8 , other authors indicate that it is problematic to consider self-reported racial discrimination as synonymous with unfair treatment without attribution 35 . In addition to allowing the examination of health effects of different types of discrimination, a broader approach to discriminatory experiences enables the assessment of theoretically relevant interactions, such as the one we observed in the present analysis, involving age, class, and skin color/race.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is significant, given that the literature on discrimination and (mental) health has emphasized unfair treatments attributed to race 5,34 . Even though a recent literature review has shown that many types of discrimination are harmful to health 8 , other authors indicate that it is problematic to consider self-reported racial discrimination as synonymous with unfair treatment without attribution 35 . In addition to allowing the examination of health effects of different types of discrimination, a broader approach to discriminatory experiences enables the assessment of theoretically relevant interactions, such as the one we observed in the present analysis, involving age, class, and skin color/race.…”
Section: Discussionmentioning
confidence: 99%
“…This assertion is also being examined in emerging research on implicit measures of individuals as targets of discrimination 35 . Our findings, however, do not necessarily contradict alternative theories postulating that attributions to discrimination may have self-protective effects 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrimination has well-documented negative consequences on mental health [20][21][22], and racial and ethnic minorities feel the effects of discrimination directly. However, American-born minorities report more experiences of discrimination compared to those foreign-born individuals [20,[40][41][42], due to heightened awareness or a different sense of social justice (compared to foreign-born), ultimately leading to a greater stress effect and higher rate of depression [21,22,40]. Consequently, although immigrants may engage in tobacco smoking and excessive alcohol consumption prior to migration, the intensity and frequency may increase as a response to discrimination and socioeconomic stress [43,44].…”
Section: Discrimination and Behavioral Factorsmentioning
confidence: 99%
“…Although there is a decreasing trend of smoking and excessive alcohol consumption in foreign-born minorities as compared to their American-born counterparts, these behaviors still persist and are germane to the outcome of depression [47][48][49][50][51]. Furthermore, discrimination and demographic measures may moderate these relationships [20,41].…”
Section: Discrimination and Behavioral Factorsmentioning
confidence: 99%